PALEOMAGNETISM OF THE 1.1 GA UMKONDO LARGE IGNEOUS PROVINCE IN SOUTHERN AFRICA - Gose W.A.; Hanson R.E.; Dalziel I.W.D.; Pancake J.A.; Seidel E.K. (My University, 2006)
The Umkondo dolerites are present over a wide area in the Kalahari craton, southern Africa. Thirty-nine sampling sites in Botswana and South Africa yielded tightly grouped paleomagnetic directions due south with shallow inclinations and three sites of opposite polarity. The dolerites have U-Pb single-crystal baddeleyite or zircon crystallization ages of 1112 ± 0.5 to 1108 ± 0.9 Ma. These results can be combined with published data from 39 additional Umkondo sites and 33 sites in the Grunehogna Province of Antarctica after restoring East Antarctica to its position next to southern Africa. Grouping the sites geographically yields 10 site mean poles with mean at 64.0°N, 38.8°E, A95 = 3.7°. This Umkondo pole can be correlated with Keweenawan poles from Laurentia. Because both sets of poles are precisely of the same age as well as predominantly of one polarity, the relative orientation of the two cratons within the Rodinia supercontinent is fixed. This implies that the Namaqua-Natal-Maud belt which rims the southern part of the Kalahari craton, faced away from Laurentia. The Umkondo pole combined with published poles suggest that the Kalahari craton remained distinctly south of the Laurend craton between 1. 1 and 1.0 Ga, making it highly unlikely that the two cratons collided. Copyright 2006 by the American Geophysical Union.